STRATEGI GURU PENDIDIKAN AGAMA HINDU DALAM MEMBENTUK KEPRIBADIAN HUMANIS PLURALIS SISWA KELAS XI DI SMA NEGERI 1 KEDIRI, TABANAN - Surya, Ida Ayu Melanie; Sueca, I Nyoman; Aryatnaya Giri, I Putu Agus (UHN IGB Sugriwa Denpasar, 2023)
The very high level of plurality that belongs to Indonesian society is a potential as well as a very big threat. Strategies that are actualized within the scope of learning can help students shape character, develop their potential towards thinking and acting critically. The Hindu Religious Education Teacher's Strategy plays a very large role in strengthening students' understanding of good and true multicultural beliefs and understanding. The aim of this study was to find out the strategy of Hindu religious education teachers in forming students' pluralist humanist personalities which later can be used as evaluation material in implementing student personality. The theories used in this research are multiculturalism, counter-stimulation theory, and humanistic theory. This research is a qualitative research with a phenomenological approach. The research location was carried out at SMA Negeri 1 Kediri, Tabanan. The technique of determining informants in this study used a purposive sampling technique with data collection in the form of observation, interviews, literature study and documentation. The collected data will be analyzed using the Miles and Huberman technique. The results of the study show that the Hindu religious education teacher's strategy in forming the pluralist humanist personality of students is through three types of activities, namely intra-curricular, extra-curricular and co-curricular activities. The role of the Hindu religious education teacher in forming the pluralist humanist personality of students is as a facilitator, motivator, mentor and educator. The challenge for teachers of Hindu religious education in shaping students' pluralist humanist personalities is to face the influence of globalization and challenges in dealing with ethnocentrism. Keywords: Strategy, Teacher, Pluralist Humanist Personality